Microstreaming inside model cells induced by ultrasound and microbubbles - Pereno, V; Lei, J; Carugo, D; Stride, E (American Chemical Society, 2020)
Studies on the bioeffects produced by ultrasound and microbubbles have focused primarily on transport in bulk tissue, drug uptake by individual cells, and disruption of biological membranes. Relatively little is known about the physical perturbations and fluid dynamics of the intracellular environment during ultrasound exposure. To investigate this, a custom acoustofluidic chamber was designed to expose model cells, in the form of giant unilamellar vesicles, to ultrasound and microbubbles. The motion of fluorescent tracer beads within the lumen of the vesicles was tracked during exposure to laminar flow (∼1 mm s–1), ultrasound (1 MHz, ∼150 kPa, 60 s), and phospholipid-coated microbubbles, alone and in combination. To decouple the effects of fluid flow and ultrasound exposure, the system was also modeled numerically by using boundary-driven streaming field equations. Both the experimental and numerical results indicate that all conditions produced internal streaming within the vesicles. Ultrasound alone produced an average bead velocity of 6.5 ± 1.3 μm/s, which increased to 8.5 ± 3.8 μm/s in the presence of microbubbles compared to 12 ± 0.12 μm/s under laminar flow. Further research on intracellular forces in mammalian cells and the associated biological effects in vitro and in vivo are required to fully determine the implications for safety and/or therapy.